2022
DOI: 10.18196/jesp.v23i1.13881
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Economic Growth and Trade Openness on Environmental Degradation: Evidence from A Panel of ASEAN Countries

Abstract: Global warming and climate change show a decrease in environmental quality. The main cause of global warming is the emission of carbon dioxide (CO2). This study aims to analyze the effect of economic growth and economic openness on environmental quality in ASEAN countries from 2010 to 2019. This research uses a panel data analysis method. The analysis results show that the variable economic growth has a negative and significant effect on carbon dioxide emissions. Meanwhile, the variables used for economic open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
4
0
2
Order By: Relevance
“…Statistical evidence reveals that FDI significantly impacts environmental degradation in G20 countries, with a p-value of 0.000, a coefficient value of 0.209, and a t-statistic value of 8.86. Previous researchers found that similar results [ 12 , 21 , 36 ]. Nevertheless, environmental diplomacy (ED) is quite influential in the cause of environmental degradation.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Statistical evidence reveals that FDI significantly impacts environmental degradation in G20 countries, with a p-value of 0.000, a coefficient value of 0.209, and a t-statistic value of 8.86. Previous researchers found that similar results [ 12 , 21 , 36 ]. Nevertheless, environmental diplomacy (ED) is quite influential in the cause of environmental degradation.…”
Section: Resultssupporting
confidence: 77%
“…However, the meaning of FDI in environmental degradation is based on the nature and operations of the investing companies and the country’s environmental regulations and policies [ 21 ]. This study A’yun [ 36 ] evaluates the relationship between ecological capital, economic growth, trade openness, and global warming in 10 ASEAN nations. The primary focus is on trade liberalization and economic development, which cause changes in carbon dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, panel data is better able to identify and measure effects that cannot be detected by cross sections or time series (Gujarati, 2012). The advantage by using the estimation of panel data is suitable for describing the dynamics of change (A'yun and Khasanah, 2022). Panel data also can measure and detect how is the impact.…”
Section: Methodsmentioning
confidence: 99%
“…Cakupan pasar negara berkembang terus berupaya meningkatkan daya tarik bagi investor asing untuk menyerap lebih banyak arus modal terlebih masuknya FDI. Menurut UNCTAD, FDI global mengalami pertumbuhan rata-rata 3,5% per tahun pada rentang 2009-2022(UNCTAD, 2022. Negara berkembang menjadi motor pertumbuhan FDI global dengan rerata 5,1% pada periode yang sama di mana catatan ini berhasil melampaui persentase pertumbuhan FDI secara global.…”
Section: Pendahuluanunclassified